Reviving the design of al-Ghazali walk and courtyard at IIUM - Safaraz, Sarah Sophia; Mohyin, Nur Affah; Yusof, Zeenat Begam; Mohamad Suhaimi, Mohamad Saifulnizam; Mohd. Din, Shamzani Affendy; Mohd. Yaman, Maheran (International Islamic University Malaysia, 2022)
The main goal of this project is to create a design that can fulfil the requirements of the project objectives. This project aims to redesign the International Islamic University Malaysia, Sultan Haji Ahmad Shah (IIUM, SHAS) Mosque’s lower floor courtyard and the road along the Al-Ghazali Walk. The selected concept for this project is ‘Iqtisad of Diversity’, which means to create a harmony of diversity in terms of the built environment and cultures found in IIUM. The idea was to elaborate on the concept of Imam Al-Ghazali in the design.